Redescription of Microcotyle elegans (Polyopisthocotyla: Microcotylidae) from Scombrops boops (Perciformes: Scombropidae) off Japanese Waters - Yusuke Kamio; Masato Nitta (Species Diversity)
Microcotyle elegans Goto, 1894 (Polyopisthocotyla: Microcotylidae) was redescribed from newly collected specimens parasitic on the gills of its type host, Scombrops boops (Houttuyn, 1782) in Japan. This monogenean has not been reported since the original description, and the holotype is believed to be lost. Morphologically, this species is most similar to M. sebastis Goto, 1894 and M. caudata Goto, 1894 in terms of the haptor shape and number of clamps, but differs from M. sebastis in the length of the genital spine, and from M. caudata in the shape of the genital atrium. The phylogenetic trees for species of Microcotyle Van Beneden and Hesse, 1863 based on the partial cytochrome c oxidase subunit I gene sequences were provided. In addition, all currently known species of Microcotyle are listed, and a key to valid species of the genus is provided.